Strateški marketing: Temeljni koncepti, metodologija in uporaba - Iršič, Matjaž (2024)
Strategic Marketing: Fundamental Concepts, Methodology and Application. Strategic way of thinking in organizations requires that they make transition from short-term planning, implementation, and control of marketing activities to strategic orientation and strategic marketing decision-making activities, directed toward creating, remaining, and enhancing their sustainable competititive advantage on the markets. In order to be effective and efficient on the field of marketing management activities, organizations should care of to find and exploit »open strategic windows«, i.e. that organizations try to harmonize their strategic competitive advantages with strategic opportunities on the markets, according to acceptable risk, manageable threats, and successful decreasing of their weaknesses in their internal environment. To realize such goal, organizations should take care on systematic and non-stop recognition of their internal and external environment as well as to invest in knowledge of key success factors on the individual markets. According to limitations, which derived from their own available resources, should they create strategic marketing objectives and implement marketing strategies, which enable them long-term market performance.
Keywords: strategic marketing; strategic analysis and diagnosis; strategic marketing planning; generic marketing strategies; fundamental marketing strategies; instrumental marketing strategies; strategic marketing plan